Administration of neem (Azadirachta indica A. Juss) leaf extract decreases TNF-α and IL-6 expressions in dextran sodium sulfate-induced colitis in rats - Ruslie, Riska Habriel; Darmadi, Darmadi (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: We aimed to determine the neem leaf extract’s effect on Tumor Necrosis Factor-alpha (TNF-α) and Interleukin-6 (IL-6) expressions in dextran sodium sulfate (DSS)-induced colitis rats. Materials and Methods: In the first phase of the study, colitis was induced by DSS administration in the case group and compared to the control group. In the second phase, 84 colitis rats were divided into groups I, II, and III receiving 7.8 mg/day of mesalazine, 100 mg/200 gm body weight, and 200 mg/200 gm body weight neem leaf extract, respectively. Results: TNF-α and IL-6 expressions were significantly increased in the case group compared to the control group. TNF-α and IL-6 expressions were decreasing in all groups receiving treatment. Group III showed an earlier decrease compared to group II. TNF-α and IL-6 expressions in group III were comparable with group I since the second week. This condition was observed in the 4th week between group II and group I. Conclusion: It can be concluded that neem leaf extract decreased the expression of TNF-α and IL-6 in DSS-induced colitis. J. Adv. Vet. Anim. Res., 7(4): 744-749, Dec 2020 http://doi.org/10.5455/javar.2020.g476